Experimental Investigation of a Laser Wireless Video Communication System Using Intensity Modulated /Direct Detection Technique - Kbashi, Hani J. (Iraqi Journal of Laser, 2010)
In this work Laser wireless video communication system using intensity modualtion direct detection IM/DD over a 1 km range between transmitter and receiver is experimentally investigated and demonstrated. Beam expander and beam collimeter were implemented to collimete laser beam at the transmitter and focus this beam at the receiver respectively. The results show that IM/DD communication sysatem using laser diode is quite attractive for transmitting video signal. In this work signal to noise ratio (S/N) higher than 20 dB is achieved in this work.